Unbiased kinome profiling identifies key and novel mediators of chronic kidney disease in hyperlipidemic mice - Bonnin-Marquez, Andrea; Maas, Sanne L.; Corcini-Berndt, Melissa; Van der Vorst, Emiel P. C. (Frontiers in Physiology, 2025)
IntroductionChronic kidney disease (CKD) is a progressive condition associated with increased mortality and morbidity, placing a substantial burden on healthcare systems globally. CKD often coexists with cardiovascular disease (CVD), further complicating patient outcomes. This study investigates the kinomic profile of hyperlipidemic mice to understand the signaling mechanisms underlying CKD progression and its cardiovascular consequences.MethodsApoe−/− mice were subjected to a Western-type diet, with or without adenine supplementation to induce CKD. Kinase activity was profiled using PamGene® assays on renal cortex samples collected at early (4 weeks) and late (12 weeks) stages of CKD.ResultsIt could be demonstrated that CKD led to significant increases in peptide phosphorylation related to both tyrosine and serine-threonine kinases, which were particularly pronounced in the late-stage model. Therefore, the kinase activity in the kidney increased upon CKD development in a CKD-stage-dependent manner. Notably, the activity of cyclin-dependent kinases (CDKs) was reduced at early disease stages but remained unaffected in late stages. Pathway analysis revealed stage-specific alterations in cell cycle regulation, inflammation, oxidative stress, lipid metabolism, and fibrosis pathways associated with kinase activity changes throughout disease progression.DiscussionThese findings highlight critical kinases involved in CKD development and suggest their potential roles in mediating pathological processes such as inflammation and fibrosis. Targeting specific kinases may offer novel therapeutic strategies for mitigating CKD progression and its cardiovascular complications. Future research should explore the causal relationships between newly identified kinases and CKD development.